Measuring parental involvement as parental actions in children’s private music lessons in China - Cui, Cancan (Frontiers in Psychology, 2023)
The purpose of this study was to establish a survey instrument to measure Chinese parents’ level of actions in their children’s private music classes. I adopted Fung’s (2018) framework of change and human actions as the theoretical support for a model of parents’ level of actions. Parents of 5- to 12-year-old children (N=894) from 20 different provinces in China were surveyed on their level of involvement (i.e., proactivity, passivity, and avoidance) in their children’s private music education. Seven factors were extracted from the exploratory factor analysis (EFA), which were then consolidated into a 3-factor solution. Confirmatory factor analysis (CFA) indicated an adequate model fit for the data collected from the Parents’ Level of Action in Private Music Learning Scale (PLAPMLS). The results from correlation analyses revealed that (1) children’s age had a direct but weak correlation with parents’ proactivity and (2) parents’ proactivity was positively associated with children’s intention to take music lessons. The results of the repeated-measures ANOVA indicated that most Chinese parents in this study were proactively involved in their children’s private music lessons. The findings from this study are consistent with the literature. Implications and recommendations are discussed, and suggestions for future research are included.